The research university, invention, and industry: Evidence from German history - Jeremiah E. Dittmar; Ralf R. Meisenzahl (Federal Reserve Bank of Chicago, 2022)
We examine the role of universities in knowledge production and industrial change using historical evidence. Political shocks led to a profound pro-science shift in German universities around 1800. To study the consequences, we construct novel microdata. We find that invention and manufacturing developed similarly in cities closer to and farther from universities in the 1700s and shifted towards universities and accelerated in the early 1800s. The shift in manufacturing was strongest in new and high knowledge industries. After 1800, the adoption of mechanized technology and the number and share of firms winning international awards for innovation were higher near universities.
Keywords: O14; O18; O30; N13; R10; I25; 330; industrialization; invention; universities; cities